Tactical sciences for biosecurity in animal and plant systems - Cardwell, Kitty Frances, 1953-; Bailey, Keith (Keith L.), 1965- (Advances in human services and public health book series., 2022)
"The primary objective of this book is to create a comprehensive look at the tactical sciences behind current biosecurity measures and dislay opportunities for improvement, exploring the sciences in both plant and animal systems to highlight the interoperability of many of the tactics, to identify synergies and gaps, and to present case studies to illustrate operations during different Biosecurity events"--